1984
DOI: 10.1177/00220345840630020301
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Repair After Condylectomy in Growing Macaca fascicularis

Abstract: In order to determine the nature of tissue repair after removal of condyles, bilateral condylectomies were performed in seven growing female Macaca fascicularis. Two animals underwent condylectomies only, and five animals were fitted with maxillary and mandibular splints before undergoing condylectomies. One condyle from each condylectomized animal was processed for histologic examination. Four animals, with intact condyles, were available as controls: Two had splints placed, while the other two did not underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
3
11
0
Order By: Relevance
“…A number of experimental studies have investigated the effect of unilateral mandibular condylectomy in animals (Sprinz, 1963;Hayes, 1967;Poswillo, 1972;Soni and Malloy, 1976;Bakker et al, 1984;Miyamoto et al, 1999aMiyamoto et al, , 2001Miyamoto et al, , 2002Miyamoto K et al, 1999). These studies have indicated that loads on the joint and articular disc, in addition to animal age, represent important factors in regeneration of the condyle.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of experimental studies have investigated the effect of unilateral mandibular condylectomy in animals (Sprinz, 1963;Hayes, 1967;Poswillo, 1972;Soni and Malloy, 1976;Bakker et al, 1984;Miyamoto et al, 1999aMiyamoto et al, , 2001Miyamoto et al, , 2002Miyamoto K et al, 1999). These studies have indicated that loads on the joint and articular disc, in addition to animal age, represent important factors in regeneration of the condyle.…”
Section: Introductionmentioning
confidence: 99%
“…Loads on the TMJ may influence regeneration of the resected condyle in animal experiments (Bakker et al, 1984;Miyamoto et al, 2002). Unilateral resection of the condylar head involves rotation and displacement of both condyles, and the loads on both TMJs change (Bakker et al, 1984;Alexandridis et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have observed the restoration process after mandible defects in various large animals such as sheep and monkeys, among others [1][2][3] . In many of these studies, transection of the mandibular head and the muscular process was performed; however, few studies have evaluated only mandibular head defects.…”
Section: Discussionmentioning
confidence: 99%